Oral health status and possible explanatory factors of an inner-city low-income community - Keith Pak-Hei Hau; Brenda Lee Currie; Samson Pak-Yan Ng; Nhu Le; Catherine Fang-Yeu Poh (Journal of Dental Sciences, 2017)
Background/purpose: Individuals with low income bear a number of health challenges to healthcare services. Vancouver's Downtown Eastside (DTES) is known to be a low-income community in a metropolitan city. Because it is difficult to reach, the oral health (OH) status of these residents is unknown. The objectives of this study are (1) to design a tool and strategy to collect OH information in a low-income community, (2) to characterize the OH status and related factors among low-income adults, and (3) to identify the explanatory factors for their OH status. Materials and methods: Mobile screening clinics were established in the gathering centers of the DTES, and those of 19 years of age or older were recruited. Data were collected through survey interviews and clinical examinations. Potential explanatory factors were investigated by regression analysis. Results: The 356 screened participants were mostly males, middle-aged, less educated, and living with low income (≤CAD$20,000/y). About 80% had dental coverage, mostly from public programs (94%). Many (86%) perceived a dental need. Among dentate participants (n=306), on average, 3.8 decayed, 8.6 missing, 4.9 filled teeth, and a care index of 41.5% were observed. Social factors (barriers to care and length of DTES residence), dental hygiene (brushing/flossing), and personal (hepatitis C virus infection/methadone usage) factors contributed to their care index level. Conclusion: This is the first time that comprehensive information regarding OH status has been collected from a low-income, inner-city community in Canada. Further investigations in the challenges and needs in accessing dental care may develop solutions for better OH in similar communities.